Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Les pensées "post-": féminismes, genres et narration - Saint-Martin, Lori; Fournier-Guillemette, Rosemarie; Ladouceur, Moana; Figura, le Centre de recherche sur le texte et l'imaginaire (Presses de l'Université du Québec, 2011)
Les pensées «post-» —parmi lesquelles on compte le postmodernisme, le postcolonialisme et ce que certains appellent le féminisme post-identitaire— marquent notre époque. Elles contestent les visions polarisées traditionnelles et favorisent l’émergence de voix jusque-là étouffées. À la lumière de ces théories, les collaboratrices du présent recueil posent des questions essentielles touchant le pouvoir et l’exclusion, les valeurs symboliques et éthiques, les enjeux narratifs et les formes textuelles. Avec des textes de Pascale Bouchard, Karine Castonguay, Rosemarie Fournier-Guillemette, Joëlle Gauthier, Jacinthe Gillet-Gelly, Moana Ladouceur et Mélissa Verreault.
Disponible en ligne à https://oic.uqam.ca/publications/publication/les-pensees-post-feminismes-genre-et-narration
Keywords: approches et analyses; arts; cours; discipline; lit2815; lit3495; postmodernisme; premier cycle; ressource en ligne; études littéraires

Reclaiming female agency: feminist art history after postmodernism - Broude, Norma..; Garrard, Mary D.; Broude, Norma; Garrard, Mary D. (University of California Press, 2005)
This volume is the third in an influential series of anthologies by editors Norma Broude and Mary D. Garrard that challenge art history from a feminist perspective. Following their Feminism and Art History: Questioning the Litany (1982) and The Expanding Discourse: Feminism and Art History (1992), this new volume identifies female agency as a central theme of recent feminist scholarship. Framed by a lucid and stimulating critical introduction, twenty-three essays on artists and issues from the Renaissance to the present, written in the 1990s and after, offer a nuanced critique of the poststructuralist premises of 1980s feminist art history.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; thématiques

Francophonie et identités culturelles - Albert, Christiane (Karthala, 1999)
L'expression littéraire est un acte puissant par lequel un être construit son identité à la fois individuellement et collectivement. Dans le contexte de la francophonie, cet acte identitaire est d'autant plus paradoxal que la langue utilisée est le français et que la littérature francophone émerge, lors de la colonisation, dans un environnement multiculturel, à partir de la déconstruction d'une littérature dominante. Afin d'interroger les multiples processus intervenant dans la constitution de l'identité francophone, un colloque a eu lieu à l'université de Pau en 1998. Il s'est achevé par une table ronde qui a réuni trois écrivains francophones : Rachid Boudjedra, Pius Ngandu Nkaashama et Tierno Monénembo qui ont évoqué la relation qu'ils entretiennent avec la langue et l'écriture. Cet ouvrage rassemble les interventions des participants à ce colloque. Tout au long de ces journées, l'identité francophone est apparue comme une configuration d'éléments multiples où la langue remplit une fonction importante. Elle ne suffit cependant pas à fonder le discours identitaire dans la mesure où elle n'est qu'un isntrument au service des écrivains. D'autres éléments apparaissent, en effet, déterminants dans l'élaboration de cette identité, éléments indissociables de l'Histoire et des développements propres à chaque société. De ce fait, l'espace littéraire francophone apparaît décentré par rapport à la langue française car il fait entendre de nouvelles voix à la périphérie de l'aire linguistique du français. Ce qui démontre, si cela était nécessaire, la richesse et la complexité de la littérature francophone, qui constitue d'une certaine façon, le laboratoire de la culture post-moderne du vingt-et-unième siècle.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; colonialisme; cours; discipline; fem1000; francophonie; haïti; identités culturelles; langage; postcolonialisme; postmodernisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; violences; études littéraires

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Les discours féminins dans la littérature postmoderne au Québec - Koski, Raija Hellevi; Kells, Kathleen Elizabeth; Forsyth, Louise (The Edwin Mellen Press, 1993)
Ce volume est une collection soigneusement choisie de textes théoriques, poétiques, analytiques et critiques. Les voix des écrivai.e.s créatif.ves, des traducteurices professionnel.l.e.s et des universitaires offrent un éventail de perspectives sur les écrivaines québécoises contemporaines. À la lumière du postmodernisme, leurs textes proposent des lectures, des appréciations et des célébrations des écritures nouvelles et expérimentales au féminin québécois des trente dernières années. De plus, la bibliographie rassemble une mine d'informations sur ces écrivaines. En français.Les discours féminins . . . examiner la problématique et les fruits de la jonction, dans un contexte québécois, des deux grands mouvements sociaux, théoriques et littéraires d'aujourd'hui : le féminisme, et le postmodernisme. Le livre fait entendre les voix émouvantes et étonnantes de Louky Bersianik, Nicole Brossard, Susanne de Lotbinière-Harwood, Daphne Marlatt et France Théoret, et font lire les textes de quatorze spécialistes de la littérature québécoise dont Janet Paterson, Karen Gould, Louise Forsyth, Lori Saint-Martin. Les auteurices du livre nous offrent l'étude de l'oeuvre d'une ou de plusieurs écrivaines ou écrivains ; elles s'intéressent aux genres littéraires et à la traduction ; elles se penchent sur la question épineuse de la théorie dans l'émergence d'une littérature et d'une culture au féminin, et aussi sur les significations problématiques des termes "féminisme" et "postmodernisme". Ce livre représente un état présent de la plus grande pertinence et utilité, une exploration collective, sous plusieurs perspectives, d'une problématique complexe et tout à fait actuel.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; littérature; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Pandora Press, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. –back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques